Integrating Boru Ni Raja Values into Character and Contextual Education in Silindung - Simbolon, Elvri Teresia; Lumbantobing, Roida; Firmando, Harisan Boni; Panjaitan, Ade Putera Arif (LP. Ma'arif Janggan Magetan, 2024)
This study addresses the urgent need to strengthen character education in response to the moral degradation caused by globalization, which has weakened students’ connection to local cultural values. It specifically aims to analyze the integration of Boru Ni Raja, a Batak Toba cultural concept that honors women as symbols of family dignity and moral integrity, into character and contextual education in the Silindung region. Using a systematic literature review guided by the PRISMA framework, 42 relevant articles published between 2015 and 2025 were analyzed to identify theoretical patterns, challenges, and opportunities for cultural integration in education. The findings reveal that Boru Ni Raja embodies values of respect, responsibility, loyalty, and social solidarity that align with the goals of 21st-century character education. The study is novel because it introduces a gender-based cultural framework, a perspective rarely discussed in previous educational literature on Batak Toba local wisdom. Academically, it contributes to expanding the theory of culture-based and gender-responsive education, while practically, it provides guidance for teachers to design contextual learning rooted in local culture. The study recommends future empirical research to validate this conceptual model in schools across Silindung and to compare it with other cultural contexts in Indonesia.